If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -49 + m = 13 Solving -49 + m = 13 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + m = 13 + 49 Combine like terms: -49 + 49 = 0 0 + m = 13 + 49 m = 13 + 49 Combine like terms: 13 + 49 = 62 m = 62 Simplifying m = 62
| 105=s-7.3 | | -25=x-18 | | -5.4=-2.5+x | | 10.8x-4.9x=-177 | | -4x-13x=119 | | 5x+7x=72 | | -103=5+9x | | 11-9x=83-23x | | -123-9x=7x+21 | | 6(2x+1)=3(x-7) | | 4x+9=24-x | | 2(x+4)=6 | | 6x+7=153-10x | | 73-2x=2x+17 | | -32-2x=10-9x | | 100-4x=10x+16 | | 4x+8=78-3x | | 3+8x=52+x | | 6x-4=15x-94 | | 5x+30=12x-54 | | 8x-28=2x+2 | | 2x+64=8x+10 | | 12x+7=6x+37 | | 5x-20=35 | | 12x+(12x*12x)= | | 13x+195=13(x+15) | | 15x+11=8x | | 12x+32=12x-7 | | 14x+5=14x-19 | | 6x+35+9x=15(x+4)-25 | | -46=3x+7x | | 16(x+2)-8=16x+24 |